2017
DOI: 10.1051/0004-6361/201630186
|View full text |Cite
|
Sign up to set email alerts
|

Planck’s dusty GEMS

Abstract: We present an analysis of high-resolution ALMA interferometry of CO(4-3) line emission and dust continuum in the "Ruby" (PLCK G244.8+54.9), a bright, gravitationally lensed galaxy at z= 3.0 discovered with the Planck all-sky survey. The Ruby is the brightest of Planck's Dusty GEMS, a sample of 11 of the brightest gravitationally lensed high-redshift galaxies on the extragalactic sub-mm sky. We resolve the high-surface-brightness continuum and CO line emission of the Ruby in several extended clumps along a part… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
58
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(62 citation statements)
references
References 71 publications
4
58
0
Order By: Relevance
“…The resulting SFR surface density we get is Σ SFR = 357 +135 −85 M yr −1 kpc −2 . These values are representative of intense star formation and are expected for the central regions of high-redshift starburst galaxies (Cibinel et al 2017;Cañameras et al 2017).…”
Section: Measurement Of the Star Formation Ratementioning
confidence: 67%
“…The resulting SFR surface density we get is Σ SFR = 357 +135 −85 M yr −1 kpc −2 . These values are representative of intense star formation and are expected for the central regions of high-redshift starburst galaxies (Cibinel et al 2017;Cañameras et al 2017).…”
Section: Measurement Of the Star Formation Ratementioning
confidence: 67%
“…Resolved t dep measurements have been carried out for only a handful of DSFGs (see Sharon et al 2019 for a recent compilation), which generally show similarly strong (∼ 1 dex) variation in t dep . The depletion times in SDP.81 are in the extreme starburst regime, an order of magnitude lower than seen in some other high-redshift DSFGs -e. Cañameras et al (2017) found a comparably low t dep (10-100 Myr) in an extreme strongly lensed z ∼ 3 starburst PLCK G244.8+54.9, albeit at much higher star-formation surface densities (ΣSFR ∼ 2 × 10 3 M yr −1 kpc −2 ). Given the extremely short depletion time in the centre of SDP.81, sustaining the high ΣSFR requires an efficient loss of gas angular momentum to feed the star formation.…”
Section: Gas Depletion Time Across the Sourcementioning
confidence: 90%
“…All GEMS have spectroscopically confirmed redshifts of z = 2.2−3.6, and apparent FIR luminosities between 5 and 27 × 10 13 µ L (Cañameras et al 2015), mainly powered by star formation and boosted by gravitational lensing from foreground clusters or massive individual galaxies by luminosityaveraged factors, µ ∼ 10−30 (Cañameras et al 2017a(Cañameras et al , 2018a. Environments probed by these galaxies range from intense, maximally star-forming clumps (Cañameras et al 2017b(Cañameras et al , 2018b to diffuse gas probed by [CII] absorption (Nesvadba et al 2016), as observed with ALMA and IRAM interferometry.…”
Section: Even Argue That [Ci] Emissionmentioning
confidence: 99%